Lingkungan Pengendalian Pengelolaan Dana Kapitasi di Puskesmas Tanjung Selor Kalimantan Utara - Anisa, Elisa Husnul; Tjaraka, Heru (IAIN Kudus, 2018)
The number of fraudulent acts on the management of capitation funds in various regions in Indonesia as a background in this study. The system was implemented by the Tanjung Selor health center and the Bulungan District Health Office in North Kalimantan in managing capitation funds without any fraud. This study using the case study method to examine the events faced in the management of capitation funds by research subjects. The findings indicate that there is not yet official regulation regarding the control system that is used as a guideline in the management of capitation funds. Control activities have been carried out, but only based on the obligations that must be carried out so that no fraud will occur.